Teaching experimental political science - Bennion, Elizabeth A. (Elgar guides to teaching., 2024)
"This insightful book delivers a wealth of innovative ideas, models, examples, and advice for teaching experimental political science in the classroom and beyond, emphasising that teaching experimental research is necessary to prepare students to succeed as researchers, practitioners, active citizens and civic leaders. It illustrates how teaching experimental methods sparks students' curiosity by allowing them to ask and answer questions about the world they live in. With a core focus on successfully engaging a diverse range of students at all levels, this book includes a variety of approaches from contributing authors who are leading scholars in their field. Chapters provide both new and experienced teachers with concrete guidance on how to: facilitate student-designed survey experiments, use workbooks and templates to overcome mathematical and writing anxiety; use mock Institutional Review Board (IRB) reviews to teach students about the ethics of experimental research; follow an apprenticeship model to teach students to carry out their own lab experiments; and train students to go out into the field. Proposed models of teaching are supported throughout by the latest empirical research on the science of learning. Teaching Experimental Political Science will be a key resource for faculty and staff working across a variety of educational contexts including political science, international relations, international politics, domestic politics, public administration and public policy"--